2019
DOI: 10.7759/cureus.5253
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Use and Abuse: Prescription Practice, Attitude, and Beliefs among Doctors of Karachi

Abstract: BackgroundOpioid analgesics, also known as narcotics, are medicinal drugs used primarily for the management of pain secondary to any type of cancer, severe injury or surgery. Due to the ease of availability, opioids are commonly abused. In 2015, reported deaths exceeded 33,000 Americans from opioid overdose. A survey in 2013 revealed nearly 1.6 million Pakistanis abusing prescription opioids for non-medical needs. Although commonly prescribed by primary care physicians, most of them are diffident to stand by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The survey also reported that 1.6 million people admitted to opioid abuse. It was also claimed that recreational drug overdosing had surpassed car accidents as the leading source of unintentional fatalities, with opioids accounting for more fatalities than cocaine and heroin [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The survey also reported that 1.6 million people admitted to opioid abuse. It was also claimed that recreational drug overdosing had surpassed car accidents as the leading source of unintentional fatalities, with opioids accounting for more fatalities than cocaine and heroin [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The primary cause of opioid addiction was the individual's mental health, which included feelings of hopelessness, curiosity, mistrust, and disinterest in social activities. Additionally, peer influences and friends may have played contributing roles in opioid use among men (Majid et al, 2019;. Furthermore, a retrospective study conducted in Pakistan revealed that the most commonly used drugs were cannabis at 29.2%, followed by cigarettes at 26.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Abuse of Tapentadol, an over-the-counter pain medication, has become commonplace in India. Nearly 1.6 million Pakistanis were found to misuse prescription opioids for non-medical purposes 6 . Pakistan is one of the top 10 countries where citizens use both prescription and non-prescribed narcotics and opiates, reported by the United Nations Office on Drugs and Violence 7 .…”
mentioning
confidence: 99%
“…The study of Zainab Majib 6 shows that the majority of opioids are prescribed against chronic pain in Karachi, Pakistan. The dosages are given on the basis of pain scale and sometimes opioids level of the Urine.…”
mentioning
confidence: 99%